Diversity and Occasional Anarchy : On Deep Economic and Social Contradictions in Hong Kong - Wong, Y. C. Richard (Yue-chim Richard), 1952- (Book collections on Project MUSE., 2013)
The world economic landscape has experienced seismic changes in the 15 years after restoration of sovereignty over Hong Kong from Britain to China. Fortunately the Hong Kong economy has remained steadfast and is still making progress, but public confidence in the governance of the SAR government has declined, and economic and social dissatisfaction have flared. Where should Hong Kong go from here in the face of all kinds of contradictions? Economist Yue-Chim Richard Wong provides an analysis of the origins of these contradictions and shares his insights on these issues. All those concerned about Hong Kong's future should not miss this collection of essays.